Analisis Kelayakan Bisnis Kue Kering “Phianz Cookies” di Kecamatan Kademangan, Kota Probolinggo (Feasibility Analysis of Pastry Business “Phianz Cookies” in Kademangan District, Probolinggo City) - Pratama, Triyan Bayu; Oktaviani, Dewi Anggun; Lidyana, Novita (Jurnal Ilmiah Sosio Agribis, 2025)
The "Phianz Cookies" cake business in Kademangan District, Probolinggo City is one of the potential culinary businesses. This study analyzes the feasibility of the business and the sensitivity of the business using primary data (owner interviews) and secondary data (literature). The research period was conducted from November to December 2024, with a cash flow analysis for 12 months The results of the study showed: NPV of IDR 10,150,000.00. Gross B/C 1.06, Net B/C 1.68, IRR 9.69% per month, Payback Period achieved in the 7th month. Sensitivity analysis revealed that profit is the most sensitive factor (27.08%), where its decline can significantly affect NPV. Thus, this business is feasible to run on the condition that it maintains or increases profits to remain sustainable. Keywords: Business Feasibility, Sensitivity Analysis, Cake Business, Phianz Cookies.